2006
DOI: 10.1074/jbc.m603248200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Transmembrane Transport for S-Nitrosocysteine-dependent Modification of Intracellular Thiols

Abstract: S-Nitrosothiols have been implicated as intermediary transducers of nitric oxide bioactivity; however, the mechanisms by which these compounds affect cellular functions have not been fully established. In this study, we have examined the effect of S-nitrosothiol transport on intracellular thiol status and upon the activity of a target protein (caspase-3), in bovine aortic endothelial cells. We have previously demonstrated that the specific transport of amino acid-based S-nitrosothiols (S-nitroso-L-cysteine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 37 publications
5
47
1
Order By: Relevance
“…Rigorous comparisons between the effects of NO and the effects of S-nitrosation on a specific cellular activity have rarely been accomplished, and NOdependent effects are often ascribed to S-nitrosation with little to no quantitative confirmatory data. We have previously demonstrated clear differences between NO and CysNO in their ability to inhibit caspase 3-like activity in doxorubicintreated bovine aortic endothelial cells (BEACs) (1). Whereas CysNO appeared to inhibit this enzyme through S-nitrosation, as has been previously proposed, we observed no inhibition upon the exposure of cells to NO.…”
Section: Nitric Oxide; S-nitrosation; S-nitrosocysteinecontrasting
confidence: 46%
See 1 more Smart Citation
“…Rigorous comparisons between the effects of NO and the effects of S-nitrosation on a specific cellular activity have rarely been accomplished, and NOdependent effects are often ascribed to S-nitrosation with little to no quantitative confirmatory data. We have previously demonstrated clear differences between NO and CysNO in their ability to inhibit caspase 3-like activity in doxorubicintreated bovine aortic endothelial cells (BEACs) (1). Whereas CysNO appeared to inhibit this enzyme through S-nitrosation, as has been previously proposed, we observed no inhibition upon the exposure of cells to NO.…”
Section: Nitric Oxide; S-nitrosation; S-nitrosocysteinecontrasting
confidence: 46%
“…Previously, we reported that CysNO could rapidly deplete GSH levels in BAECs (1). Figure 3B shows that immediately after CysNO treatment (0 h recovery), the GSH levels were increased at low micromolar levels of CysNO, but above 40 M CysNO, GSH was substantially depleted in a concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 86%
“…29 Extracellular levels of RSNO can also influence intracellular thiol levels by the transport of a low-molecular-weight RSNO, thus representing a different method of RSNO influx independent of NO generation. 30 …”
Section: No Transport and Thiol Modificationmentioning
confidence: 99%
“…High levels of NO donor will not only limit selectively, but also have the potential to compromise the cellular reducing systems thus stabilising S-nitrosothiols, allowing them to accumulate at a higher concentration. S-nitrosocysteine is known to deplete GSH levels in a concentration-dependent manner in multiple cell types [131,132]. Severe depletion of the reduced thiol pool was shown to generate non-physiological levels of intracellular S-nitrosothiols.…”
Section: Use Of No Donors In the Study Of Protein S-nitrosationmentioning
confidence: 99%